Efeito do tratamento de sementes de tomateiro (Solanum lycopersicum L.) com óleo essencial de Origanum vulgare L. e carvacrol na incidência da murcha de fusarium em mudas. - Gonçalves, Débora Cristina (2018)
Tomato plants can be grown in several regions of the world due to its adaptability to different climate types. This crop is susceptible to a series of diseases that reduce the tomato production, among them Fusarium wilt stands out as one of the most impor